Real-time bus crew scheduling using multi-agents system - Eldabi, Tillal; Rzevski, George; Shibghatullah, Abdul Samad (2006)
Bus crew scheduling problem is notoriously difficult to solve because of the large number of resources that need to be allocated, very complex rules for the allocation of crew shiﬁs, high cost of overtime and unpredictability of the urban traﬂic and crew availability. Current schedulers are reviewed and critiqued. The paper considers an alternative approach to the bus crew allocation based on the use of multi- agent systems capable of real-time scheduling and dynamic re-scheduling whenever an unpredictable change of resources or demands occurs.